CIVIL LAW AND CIVIL PROCEDURE EDUCATION FOR THE COMMUNITY: BUILDING LEGAL AWARENESS IN ECONOMIC TRANSACTIONS - Ning Adiasih; Gandes Candra Kirana; Indra Krestianto; Rinandu Kusumajaya Ningrum; Ramadhana Bachry (Universitas Pahlawan Tuanku Tambusai, 2025)
The significance of legal education, particularly in the realms of civil law and civil procedure law, cannot be overstated in fostering legal awareness among the public. This paper aims to examine the role of civil law education and civil procedure law education in enhancing public legal consciousness within economic transactions. By employing a qualitative analytical approach, this study delves into the theoretical frameworks that support legal education and explores empirical evidence from various studies published in the past five years. The analysis demonstrates that a robust understanding of civil law and civil procedure law can empower individuals to navigate economic transactions more effectively, thereby reducing legal disputes and enhancing economic stability. The paper also discusses the challenges and barriers in implementing effective legal education programs and proposes recommendations for improving the public's legal awareness. Ultimately, this research underscores the necessity of integrating comprehensive legal education into public education systems to build a more legally informed society